Heterogeneity of social classes and job accessibility: implications of transport policies in Bogota - Carlos Augusto Olarte Bacares (European Regional Science Association (ERSA), 2011)
Several researches have been done about transport in Bogotá (Colombia) but no one has treated the impact of the transport network on the configuration of employment in the city. This research has two different aims which are directly interrelated. The definition of the effective size of labor market in the city is necessary to sheds light on the relation of transport accessibility and type of jobs or social classes within different zones in Bogotá. We support the first part of our study on the existing literature about the effective size of labor market. Under the specification of a conceptual model, we want to demonstrate the significant correlation (even causality) between accessibility and type of jobs in Bogotá. In order to capture the possible endogeneity among transport' accessibility and type of jobs we will use a Structural Equation Modeling (SEM). Results will give us enough tools to know if transport network' accessibility, jobs' accessibility and type of jobs (or social classes) are large interrelated or not in the city of Bogotá. It will also let us to know if improvement of public network infrastructures traduced in a tacit enhancement on accessibility has a positive effect on incomes of inhabitants. We will understand the degree of correlation between accessibility to public transports and accessibility to jobs with respect to type of jobs and/or social class of labor force. Actually, first results show us that, there is a direct relationship between socio-economic class and time accessibility to jobs; the more accessibility of public transport system is in a zone of the city, the best is the social class and the better are the type of jobs of inhabitants so the highest will be the income. Nevertheless, it is observed (but not proved yet) that in some zones of the city where accessibility index is high, social class and types of jobs of inhabitants connected and living in these zones are not the best ones. Even so, we hope that with our methodology and data we could collect, we will be able to elucidate our research question.
Keywords: 330